THE EFFECTIVENESS OF USING TED TALKS TO IMPROVE STUDENTS’ PRONUNCIATION AT THE TWELFTH GRADE STUDENTS OF SMK MUHAMMADIYAH WAY SULAN IN 2016-2017 - Mutiatus Saniyati; Yanuarius Yanu Dharmawan (Universitas Bandar Lampung, 2016)
This research described the use of TED Talks to improve students’ pronunciation. Moreover, it was to find outwhether TED Talks is effective to improve students’ pronunciation at the twelfth grade students of SMKMuhammadiyah Way Sulan. This research used experimental design in which attitudes were assessed both beforeand after an experimental treatment. The subject of the research was consisted of 60 students, they were dividedinto experimental and control group. The instruments used for collecting data were test which was consisted ofpretest and posttest. The data analysis of this research was attempted by using independent sample T-test whichwas calculated through computing with Statistical Package for Social Science (SPSS) version 20. The resultindicated that the students’ mean score of experimental and control group in posttest were significantly different.It showed that t-count was higher than t-table (10,706 > 2,002) and the sig. 2-tailed value was lower than sig. level(0.000 > 0.05). Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.It meant that there was effective impact of using TED Talks towads students’ pronunciation. In conclusion, usingTED Talks as a media was effective to improve students’ pronunciation. Therefore, it was suggested the use ofTED Talks as a media in teaching English generally and teaching pronunciation particularly.